ANALISIS PERUBAHAN PENGGUNAAN LAHAN PERTANIAN PRESISI DENGAN METODE OBIA (Studi Kasus Di Kecamatan Dramaga, Kabupaten Bogor) - Yanuarsyah, Iksal (Fakultas Teknik dan Sains, Universitas Ibn Khaldun Bogor, 2015)
The current development of Bogor Regencyespecially in Dramaga Sub-district is very rapidly. Landusechange activities was occurred by converting forest or vegetationarea, farm field, bareland, particularly in agricultural landconverted into settlements, office cluster and industrial area.Beside of many methods due to analyze landuse change, remotesensing is one approach to do so more powerful. Remote sensingis not only relying on imagery with respected to the accuracy andquality of data, but also followed by extraction technique withwhich is an Object-Based Image Analysis (OBIA). OBIA is oneprecisely technique to extract information from imagery by usingmultiresolution segmentation based on certain parameters (suchas cale parameter, color, shape factor, compact, dan smooth, etc).The imagery extraction result by using OBIA provides objectbasedclassification parameters thus to calculate precisely thechange of agricultural land (such as farm fields and paddy field)are converted into developed land.